Prediction of major trends of transportation development - Mazūra, Mindaugas (Transport, 2002)
The importance of forecasting the economic characteristics of transportation (i.e. the amount of freight and passengers carried, the turnover rate of freight and passengers, etc. in transportation as a whole and in particular areas using various transport facilities) is demonstrated. Methods for predicting the development of transportation based on multidimensional regression and correlation analysis and realizing mathematical models for finding linear and non-linear multidimensional regression equations as well as a mathematical model for choosing linear and non-linear regression equations, more accurately approximating the empirical data, are presented. The techniques aimed to obtain and apply the linear correlation coefficient and correlative relationship in determining the forecast accuracy is also given. The efficiency of methods, determining the linear correlation coefficient and correlative relationship, used in achieving higher accuracy of forecasts is shown. First Published Online: 19 Oct 2011